Design of whey protein aggregates towards microgel-stabilized emulsion generation - Niizawa, Ignacio (2021)
Whey protein aggregates (WPAg) were designed from whey protein concentrate suspensions adjusting thermal treatment conditions to prepare microgel-stabilized emulsions. The response surface methodology (RSM) was used to design WPAg with different characteristics (size, denaturation degree, and exposure degree of surface thiol groups), considering the effect of temperature (67.9 °C - 83.1 °C), protein concentration (3.49% w/w - 6.01% w/w), and pH (6.49 - 7.76) conditions throughout the thermal aggregation process. Three types of WPAg with markedly different characteristics were obtained using the RSM models to evaluate the influence of different protein aggregates on microgel-stabilized emulsions. These microgel particles successfully stabilized the emulsions against coalescence during 14 days of storage, particularly at pH 4.7 and 7.